Ethical and cultural implications for conducting verbal autopsies in South and Southeast Asia: a qualitative study - Shaun K Morris; Yoel Lubell; Prabhat Jha; Rusheng Chew; Phaik Yeong Cheah; Rupam Tripura; Anne Osterrieder; Thomas J Peto; Nan Shwe Nwe Htun; Carlo Perrone; Aung Pyae Phyo; Aninda Sen; et al. (BMJ Global Health, 2023)
Introduction Causes of deaths often go unrecorded in lower income countries, yet this information is critical. Verbal autopsy is a questionnaire interview with a family member or caregiver to elicit the symptoms and circumstances preceding a death and assign a probable cause. The social and cultural aspects of verbal autopsy have gotten less attention than the technical aspects and have not been widely explored in South and Southeast Asia settings.Methods Between October 2021 and March 2023, prior to implementing a verbal autopsy study at rural sites in Bangladesh, Cambodia, Laos, Myanmar and Thailand, focus group discussions were conducted with village heads, religious leaders and community members from varied demographic backgrounds. Thematic analysis elucidated customs and traditional views surrounding death to understand local ethnocultural sensitivities.Results We found that death rituals varied greatly among religions, ethnicities and by socioeconomic status. Mourning periods were reported to last 3–100 days and related to the cause of death, age and how close the deceased person was to the family. Participants advised that interviews should happen after mourning periods to avoid emotional distress, but not long after so as to avoid recall bias. Interviewers should be introduced to respondents by a trusted local person. To provide reassurance and confidentiality, a family’s residence is the preferred interview location. Interview questions require careful local language translation, and community sensitisation is important before data collection.Conclusion Verbal autopsy is acceptable across a wide range of cultural settings in Southeast Asia, provided that local norms are preidentified and followed.